2019
DOI: 10.35950/cbej.v25i104.4651
|View full text |Cite
|
Sign up to set email alerts
|

مـــعايير الــدورة الدمويــة في الجــهاز الـدوري لمجاميع مختلفــة من الطلبــة الاجــانب مع اختلافــات التنظيــم اللاإرادي لــمعدل ضربات القلــب

Abstract: Under physiological conditions, the first years of university studies of the students of Arabic and African subgroups with moderate parasympathetic autonomous regulation)  MPAR( and self-regulation )SR( were characterized by toughness, low effectiveness of the system of blood circulation, increased peripheral vascular resistance, vascular type of self-regulation of blood circulation )TSC (; Indian and Latino-American subgroups with MPAR SR revealed the weakness and low efficiency of the circulatory system, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Comparative functional studies of male and female students the main and control groups revealed higher systolic and diastolic blood pressure and heart rates in students from India in all seasons. Similar changes in autonomic functions in the form of increased blood pressure and heart rate were noted in first year students who came from humid and sub-tropical countries [77]. Foreign students have less functional reserves, which is leads to more frequent development of maladaptive reactions, as well as more frequent detection of acute respiratory and intestinal infections in their first year.…”
Section: Discussionmentioning
confidence: 60%
“…Comparative functional studies of male and female students the main and control groups revealed higher systolic and diastolic blood pressure and heart rates in students from India in all seasons. Similar changes in autonomic functions in the form of increased blood pressure and heart rate were noted in first year students who came from humid and sub-tropical countries [77]. Foreign students have less functional reserves, which is leads to more frequent development of maladaptive reactions, as well as more frequent detection of acute respiratory and intestinal infections in their first year.…”
Section: Discussionmentioning
confidence: 60%